2006
DOI: 10.1016/j.ultrasmedbio.2006.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Improved visualization of high-intensity focused ultrasound lesions

Abstract: Spectral parameter imaging in both the fundamental and harmonic of backscattered radiofrequency (RF) data was used for immediate visualization of high-intensity focused ultrasound (HIFU) lesion sites. A focused 5-MHz HIFU transducer with a coaxial 9-MHz focused single-element diagnostic transducer was used to create and scan lesions in chicken breast and freshly excised rabbit liver. Bmode images derived from the backscattered RF signal envelope were compared with midband fit (MBF) spectral parameter images in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Early studies on the use of ultrasound-induced hyperthermia (1–2 W/cm 2 , 30 min) for treatment of melanoma tumor xenografts showed that treated tissue had a significant decrease in spectral slope by 0.480 dB/MHz and a significant increase in intercept by more than 10 dB as compared to untreated tissue (Silverman et al 1986). Later work by the same group reported changes in spectral parameters on lesions induced by HIFU in ex-vivo liver (700 W/cm 2 , 5 s) (Lizzi et al 1997) and more recently in ex-vivo chicken breast and rabbit liver (5.6–10 kW /cm 2 , 15–30 s) (Silverman et al 2006). The ablated tissue in these studies exhibited midband fit of 6 to 8 dB higher than surrounding tissue, with further enhanced contrast of ~12 dB when the MBF was computed from the second harmonic signal (Silverman et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies on the use of ultrasound-induced hyperthermia (1–2 W/cm 2 , 30 min) for treatment of melanoma tumor xenografts showed that treated tissue had a significant decrease in spectral slope by 0.480 dB/MHz and a significant increase in intercept by more than 10 dB as compared to untreated tissue (Silverman et al 1986). Later work by the same group reported changes in spectral parameters on lesions induced by HIFU in ex-vivo liver (700 W/cm 2 , 5 s) (Lizzi et al 1997) and more recently in ex-vivo chicken breast and rabbit liver (5.6–10 kW /cm 2 , 15–30 s) (Silverman et al 2006). The ablated tissue in these studies exhibited midband fit of 6 to 8 dB higher than surrounding tissue, with further enhanced contrast of ~12 dB when the MBF was computed from the second harmonic signal (Silverman et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Later work by the same group reported changes in spectral parameters on lesions induced by HIFU in ex-vivo liver (700 W/cm 2 , 5 s) (Lizzi et al 1997) and more recently in ex-vivo chicken breast and rabbit liver (5.6–10 kW /cm 2 , 15–30 s) (Silverman et al 2006). The ablated tissue in these studies exhibited midband fit of 6 to 8 dB higher than surrounding tissue, with further enhanced contrast of ~12 dB when the MBF was computed from the second harmonic signal (Silverman et al 2006). The aforementioned values of change in midband fit, intercept, and slope are in line with the trends reported for the corresponding threshold values in this study (+3.3 dB, +7.8 dB, and −0.17 dB/MHz), and quantitatively close to the optimal thresholds determined in this study for temporal maximum midband fit Δ M max of +11 dB and temporal minimum slope of −0.50 dB/MHz (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment planning requires a good understanding of the acoustic field, and at the high intensities needed to thermally ablate tissue, the effect of nonlinearity cannot be ignored. Likewise, potential ultrasound-based treatment monitoring methods such as tissue harmonic imaging rely on detecting nonlinear acoustic phenomena in tissue [3].…”
Section: Introductionmentioning
confidence: 99%
“…Spectrum analysis of backscattered radio-frequency (RF) ultrasound signals in US imaging 19-23 has also been exploited for objective, quantitative tissue characterization. The method has proven to be effective for identifying tissue changes due to prostate cancer, 24-26 breast cancer, 27 ocular cancer, 28 lymph node metastases from cancers of the breast 29 and colon, 30-33 liver disease, 34 intravascular plaque, 35 and hyperthermic lesions 36-38 and has also been implemented to perform real-time tissue-type imaging. 39 In brief, the method of spectrum analysis extracts parameters from the ultrasound backscattered from local inhomogeneities in tissue.…”
Section: Introductionmentioning
confidence: 99%